Review of the Certification Procedure for Qualified Persons of Manufacturers of Medicines for Human Use in Russia - Zh. I. Aladysheva; N. V. Pyatigorskaya; V. V. Beregovykh; G. E. Brkich; A. P. Meshkovskiy; M. M. Marshalova; V. V. Belyaev; N. S. Nikolenko; E. I. Nesterkina; A. A. Kamaletdinova; M. F. Lutfullin (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Scientific relevance. In December 2020, the Russian Federation adopted the Eurasian Economic Union (EAEU) requirements. This has significantly changed the certification procedure for qualified persons (QPs) of manufacturers of medicinal products for human use in the Russian Federation. To accommodate these changes, the Russian regulatory framework needs further improvement.Aim. This study aimed to review the changes made to the mechanism of state regulation of medicines and to evaluate the impact on the pharmaceutical industry two years after the adoption of the current QP certification procedure.Discussion. This review compares two QP certification procedures established by Order No. 7n of the Ministry of Health of the Russian Federation dated 12 January 2021. The first is an abbreviated one for QPs certified under the previous procedure, and the second is an initial one for QPs being certified for the first time, having an expired certificate, or wishing to extend their professional qualification profiles. The article illustrates common mistakes made by certification applicants when preparing their documents. Furthermore, the authors describe the most prevalent knowledge gaps identified by testing. The abbreviated certification procedure ensured a sufficiently smooth transition to the EAEU requirements. For example, by 1 February 2023, 506 QPs were recertified for the next five-year period according to this procedure. This accounts for slightly more than half of all QPs certified in the Russian Federation according to the previous requirements. The total number of QPs certified according to the EAEU requirements in Russia in 2021–2022 is approximately 1.5 times higher than the number of QPs certified during the same period in 2014–2015.Conclusions. The updated procedure for QP certification has noticeably changed the occupational group of QPs formed in the Russian Federation in the last decade. The implementation of the new QP certification procedure has revealed several procedural issues that require additional explanation and clarification by the Ministry of Health of the Russian Federation.